2015
DOI: 10.1007/s10488-015-0672-7
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Leader and Follower Ratings of Transformational Leadership: Relationship with Organizational Culture in Mental Health

Abstract: The role of leadership in the management and delivery of health and allied health services is often discussed but lacks empirical research. Discrepancies are often found between leaders’ self-ratings and followers’ ratings of the leader. To our knowledge no research has examined leader–follower discrepancies and their association with organizational culture in mental health clinics. The current study examines congruence, discrepancy, and directionality of discrepancy in relation to organizational culture in 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 56 publications
3
56
0
1
Order By: Relevance
“…For example, feedback is provided during annual performance reviews and for guidance on performance of assigned tasks and duties. This begs the question of how leader self-perceptions and provider perceptions of the leader may impact organizational culture and climate (Aarons, Ehrhart, Farahnak, Sklar, & Horowitz, In press; Ehrhart, Schneider, & Macey, 2014). For example, discrepancies in ILS ratings in mental health are associated with feedback climate (Aarons, Ehrhart, Torres, Finn, & Beidas, In review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, feedback is provided during annual performance reviews and for guidance on performance of assigned tasks and duties. This begs the question of how leader self-perceptions and provider perceptions of the leader may impact organizational culture and climate (Aarons, Ehrhart, Farahnak, Sklar, & Horowitz, In press; Ehrhart, Schneider, & Macey, 2014). For example, discrepancies in ILS ratings in mental health are associated with feedback climate (Aarons, Ehrhart, Torres, Finn, & Beidas, In review).…”
Section: Discussionmentioning
confidence: 99%
“…Third, leadership ratings in this study were only from the persepectives of staff about their immediate supervisor. There may be discrepancies between leader and follower ratings that can affect organizational culture or climate (Aarons et al, In press). Finally, as the organizational structure of substance use treatment programs are typically multilevel, future research should examine supervior and staff perceptions of the implementation leadership for middle and upper-level management.…”
Section: Discussionmentioning
confidence: 99%
“…The Cronbach’s alphas from the present study indicated excellent reliability for transformational leadership (α=0.96) and passive-avoidant leadership (α=0.86), and good reliability for transactional leadership (α=0.76). The validity of the MLQ is supported by studies demonstrating its associations and prediction of important organizational outcomes including change in practice (Leithwood & Jantzi, 2006), attitudes toward EBIs and capacity to train providers and implement EBIs (Aarons, 2006; Bonham, Sommerfeld, Willging, & Aarons, 2014), organizational culture (Aarons, Ehrhart, Farahnak, Sklar, & Horowitz, In press), knowledge sharing (Chen & Barnes, 2006), employee creativity (Dhar, 2015; Jyoti & Dev, 2015), innovation performance (Saad & Mazzarol, 2014), enhanced EBI receptivity, ongoing use, and ability to implement and sustain EBIs (Stetler, Ritchie, Rycroft-Malone, Schultz, & Charns, 2009), organizational climate expectations (von Thiele Schwarz, Hasson, & Tafvelin, 2016), and patient and consumer outcomes (Corrigan, Lickey, Campion, & Rashid, 2000; Wong & Giallonardo, 2015). Home visitors indicated the extent to which their supervisor exhibited specific behaviors on a 5 point Likert-type scale from “Not at all” to “To a very great extent.” Individual leadership scores were computed as item averages.…”
Section: Methodsmentioning
confidence: 99%
“…Although these studies have added to an understanding of the different types of disagreement, there has been limited research specifically focusing on leadership discrepancy and its effect on outcomes such as organizational climate. This is an important area of inquiry as recent work has shown that mental health leader-follower discrepancies in transformational leadership ratings can negatively affect organizational culture (35). …”
Section: Introductionmentioning
confidence: 99%